Mutagenic biomarkers in erythrocytes of free-ranging and captive Kinosternon scorpioides from the Brazilian Amazon - Carlos Alailson Licar Rodrigues; Almerinda Macieira Medeiros; Elizângela Pinheiro Pereira; Katherine Saldanha Noleto; Raimunda Nonata Fortes Carvalho Neta; Germán Augusto Murrieta Morey; Alana Lislea de Sousa (Ciência Animal Brasileira)
This study aimed to investigate the occurrence of micronuclei (MN) and erythrocyte nuclear abnormalities (ENAs) in natural and captive Kinosternon scorpioides populations and compare their frequencies with the environment type, sex, and seasonal period in an environmental protection area in the state of Maranhão, Amazon. Blood was collected from 112 specimens from regions with direct anthropogenic influence and indirect and control areas to produce blood smears for subsequent cytological analysis under an optical microscope. We found MN (N=91) and ENAs such as binucleated nuclei (N=14), notched (N=81), lobulated (N=35), segmented (N=16), and displaced (N=253) in animals in situ. No abnormalities were recorded in the erythrocytes of the captive specimens. The mean (±standard deviation) MN (1.13±0.47) differed from those of the other chelonians from the natural environment, and the displaced and binucleated nuclei manifested themselves at higher (51.6%) and lower (2.8%) frequencies, respectively. Lobulated nuclei frequency was significantly different between the areas (p<0.05); segmented nuclei (p<0.05) and displaced (p<0.05) had higher frequencies during the dry and rainy periods. Sex did not affect these abnormalities. No significant MN were found; however, erythrocytes with lobulated, segmented, and displaced nuclei were documented in animals from different environments and seasonal periods. Our study provides pioneering data on MN and nuclear anomalies in the erythrocytes of K. scorpioides and confirms the significant differences and relationships between them. The occurrence of abnormalities in wild animals demonstrates the need to maintain protected areas and the continuity of conservation actions aimed at Amazonian turtles. This contributes to reducing the impact on conservation units that employ the sustainable use of biodiversity in Brazil.